2013
DOI: 10.1016/s0924-9338(13)76615-x
|View full text |Cite
|
Sign up to set email alerts
|

1620 – Blood lipid spectrum changes in first-episode schizophrenia patients treated with risperidone and haloperidol

Abstract: The aimComparative study of the blood lipid spectrum changes in first-episode schizophrenia patients treated with risperidone and haloperidol.Materials and methods68 patients with first-episode schizophrenia (average age 24,9 years) and 20 age-matched normal controls were investigated. All patients had PANSS total score not less than 80 points. The patients were divided in two groups of 34 persons in each group: treated with haloperidol and risperidone. Total cholesterol (TC), high-density lipoprotein choleste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…ApoA1 is the main protein component of HDL, and a biomarker of cardiovascular disease [31], while ApoB is the main protein including plasma chylomicrons, verylow-density lipoprotein (VLDL) and LDL [32], which can be used as a biomarker of schizophrenia [33]. On the one hand, numerous studies have observed the mixed changes in ApoA1 and ApoB levels in patients with schizophrenia, such as an increase in ApoA1 [31,34,35] or ApoB [33,36,37] and reduction of ApoA1 [37,38], or ApoB [35]. On the other hand, ApoA1 and ApoB levels may be associated with cognitive decline [39,40], which has been indirectly verified by a number of mouse experiments [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…ApoA1 is the main protein component of HDL, and a biomarker of cardiovascular disease [31], while ApoB is the main protein including plasma chylomicrons, verylow-density lipoprotein (VLDL) and LDL [32], which can be used as a biomarker of schizophrenia [33]. On the one hand, numerous studies have observed the mixed changes in ApoA1 and ApoB levels in patients with schizophrenia, such as an increase in ApoA1 [31,34,35] or ApoB [33,36,37] and reduction of ApoA1 [37,38], or ApoB [35]. On the other hand, ApoA1 and ApoB levels may be associated with cognitive decline [39,40], which has been indirectly verified by a number of mouse experiments [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…The median ApoA1 and ApoB levels of health controls were 1.19 g/L and 0.86 g/L in the Africans, 1.15 g/L and 0.98 g/L in the Arabs, 1.23 g/L and 0.83 g/L in the Chinese, 1.26 g/L and 0.95 g/L in the Europeans, 1.18 g/L and 0.95 g/L in the Latin Americans, 1.07 g/L and 0.92 g/L in the South Asians, and 1.29 g/L and 0.96 g/L in the Southeast Asians, respectively [ 34 ]. A large number of studies have observed changes in the levels of ApoA1 and ApoB in patients with schizophrenia, with mixed results, such as elevated ApoA1 [ 31 , 35 , 36 ] or ApoB [ 37 39 ], which can be used as biomarkers of schizophrenia [ 39 ] as well as decreased ApoA1 [ 38 , 40 ] or ApoB [ 36 ]. In addition, ApoE gene polymorphism may affect the expression levels of ApoA1 and ApoB [ 41 43 ].…”
Section: Introductionmentioning
confidence: 99%